A ética do sentido da vida na logoterapia de Viktor Frankl - Pereira, Ivo Studart (2009)
The present work aimed to research the theoretical interfaces between ethics and psychology in the opus of Viktor Frankl, Austrian psychiatrist and founder of Logotherapy. Through the systematization of three concepts (“meaning”, “will to meaning” and “moral conscience”), our analytical path led us to the description of a “meaning-of-life ethics” as an “ethic of responsibility” that reconciles morals and ontology. The first category is interpreted as a key concept in order to enlighten Frankl’s world view. In the next chapter, divided in two parts, the anthropological theory of Logotherapy is studied in detail. The third concept brings forth the problem of meaning legitimacy as a moral imperative. At this point we face Frankl’s radical ontological questioning on the phenomenon of responsibility. The last chapter attempts to harmonize the three categories mentioned into an ethical theory.